Stranded humpback whale (Megaptera novaeangliae) (Cetacea: Balaenopteridae) in Paraná River Delta, Buenos Aires Province, Argentina. Comments on the occurrence of marine mammals in the La Plata River Basin - Lucero, Sergio; Gariboldi, María Constanza; Bauni, Valeria; Meluso, Juan Manuel; del Castillo, Daniela Laura; Agnolin, Federico; Bogan, Sergio (Papéis Avulsos de Zoologia)
The humpback whale (Megaptera novaeangliae) is distributed among most oceans and seas of the globe (except Mediterranean Sea). These whales migrate from feeding regions in the Antarctic waters to breeding areas in tropical and subtropical seas. Here we report the stranding of a female young humpback whale, which was founded dead in the vicinity of the Talavera Island, in the Paraná River Delta, Buenos Aires Province, Argentina. From the analysis of mitochondrial cytochrome c oxidase subunit I gene sequences, two novel haplotypes were found, totalizing four haplotypes described for the species. In the La Plata River Basin this species was found only twice at the end of the XIX century. Thus, the new finding constitutes an important addition to the list of cetaceans that occurs in Uruguay, Paraná and La Plata Rivers. Fil: Lucero, Sergio. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales “Bernardino Rivadavia”; Argentina Fil: Gariboldi, María Constanza. Universidad Maimónides. Área de Investigaciones Biomédicas y Biotecnológicas. Centro de Estudios Biomédicos, Biotecnológicos, Ambientales y de Diagnóstico; Argentina Fil: Bauni, Valeria. Fundación de Historia Natural Félix de Azara; Argentina Fil: Meluso, Juan Manuel. Fundación de Historia Natural Félix de Azara; Argentina Fil: del Castillo, Daniela Laura. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales “Bernardino Rivadavia”; Argentina Fil: Agnolin, Federico. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales “Bernardino Rivadavia”; Argentina Fil: Bogan, Sergio. Fundación de Historia Natural Félix de Azara; Argentina